Rey Auditory Verbal Learning Test of University Students - Margaretha Sih Setija Utami; Augustina Sulastri; Haryo Guritno (Universitas Katolik Soegijapranata, 2019)
This research aimed to study the relationship between age and sex with each subtest of the RAVLT- Rey 1964 version. There were 108 students participated in this research. Their ages ranged from 18-38 year old. There were 40 male and 68 female participants. The results of the research showed that there were significant negative correlations between age and short term retention (r= -0.215 p< 0.05), and long term memory (r = -0.283, p0.05). There was no significant differences between male and female participants on the three results of the RAVLT. However, we found that there were signifantly differences between male and female students on trial A4 score tM-F= -2,746, p